Use of the novel contact heat evoked potential stimulator (CHEPS) for the assessment of small fibre neuropathy: correlations with skin flare responses and intra-epidermal nerve fibre counts - Atherton, D; Facer, P; Roberts, K; Misra, V; Chizh, B; Bountra, C; Anand, P (BioMed Central, 2007)
Background: The Contact Heat Evoked Potential Stimulator (CHEPS) rapidly stimulates cutaneous small nerve fibres, and resulting evoked potentials can be recorded from the scalp. We have studied patients with symptoms of sensory neuropathy and controls using CHEPS, and validated the findings using other objective measures of small nerve fibres i.e. the histamine-induced skin flare response and intra-epidermal fibres (IEF), and also quantitative sensory testing (QST), a subjective measure. Methods: In patients with symptoms of sensory neuropathy (n = 41) and healthy controls (n = 9) we performed clinical examination, QST (monofilament, vibration and thermal perception thresholds), nerve conduction studies, histamine-induced skin flares and CHEPS. Skin punch biopsies were immunostained using standard ABC immunoperoxidase for the nerve marker PGP 9.5 or the heat and capsaicin receptor TRPV1. Immunoreactive IEF were counted per length of tissue section and epidermal thickness recorded. Results: Amplitudes of Aδ evoked potentials (μV) following face, arm or leg stimulation were reduced in patients (e.g. for the leg: mean ± SEM – controls 11.7 ± 1.95, patients 3.63 ± 0.85, p = 0.0032). Patients showed reduced leg skin flare responses, which correlated with Aδ amplitudes (rs = 0.40, p = 0.010). In patient leg skin biopsies, PGP 9.5- and TRPV1-immunoreactive IEF were reduced and correlated with Aδ amplitudes (PGP 9.5, rs = 0.51, p = 0.0006; TRPV1, rs = 0.48, p = 0.0012). Conclusion: CHEPS appears a sensitive measure, with abnormalities observed in some symptomatic patients who did not have significant IEF loss and/or QST abnormalities. Some of the latter patients may have early small fibre dysfunction or ion channelopathy. CHEPS provides a clinically practical, non-invasive and objective measure, and can be a useful additional tool for the assessment of sensory small fibre neuropathy. Although further evaluation is required, the technique shows potential clinical utility to differentiate neuropathy from other chronic pain states, and provide a biomarker for analgesic development.